Pricing cat bonds for cloud service failures - Loretta Mastroeni; Alessandro Mazzoccoli; Maurizio Naldi (Journal of Risk and Financial Management, 2022)
The use of the cloud to store personal/company data and to run programs is gaining wide acceptance as it is more efficient and cost-effective. However, cloud services may not always be available, which could lead to losses for customers and the cloud provider (the provider is typically obligated to compensate its customers). It can protect itself from such losses through insurance, which transfers the risk to the insurer. In the case of poor cloud availability, the amount that the insurer has to pay back to the cloud provider may become so high that it endangers the insurer's financial solvency. We propose the use of cat bonds as reinsurance tools as well as the Nowak-Romaniuk pricing scheme. The outage frequency was described by the Poisson process and the loss severity was described by a Pareto random variable; we derived a closed formula for the price of a cat bond in a stochastic interest rate environment, using both one-factor and two-factor short-rate models. We demonstrated the applicability of our pricing formula in a real context.
Keywords: 650; cyber-risks; cat bond; financial pricing; cyber-insurance